Integration of PK/PD for dose optimization of Cefquinome against Staphylococcus aureus causing septicemia in cattle - Ahmad, Ijaz; Hao, Haihong; Huang, Lingli; Sanders, Pascal; Wang, Xu; Chen, Dongmei; Tao, Yanfei; Xie, Shuyu; Xiuhua, Kuang; Li, Juan; Dan, Wan; Yuan, Zonghui (Frontiers in Microbiology, 2015)
Cefquinome is a fourth generation cephalosporin with antimicrobial activity against gram negative and gram positive bacterial species, including Staphylococcus aureus. The aim of our study was to observe the ex vivo activity of cefquinome against Staphylococcus aureus strains by using bovine serum from intravenously treated cattle. Cefquinome kinetics were measured by liquid chromatography and UV detection. In vitro post antibiotic effects (PAEs) and mutant prevention concentrations were determined with S. aureus strain ATCC 12598. Cefquinome exhibited time-dependent killing and produced in vitro PAEs increasing with concentration and time of exposure. A pharmacokinetic-pharmacodynamic model was established to simulate the efficacy of cefquinome for different dosage regimens. A dosage of 2 mg/kg every 12h for three days was expected to reach a bactericidal activity against S. aureus in case of septicemia.